ANALYSIS OF PARENT-CHILD RELATIONSHIPS IN FAMILIES IN LITERATURE: EMOTIONAL STATE OF SCHOOL-AGED CHILDREN (Innovate Conferences, 2025)
This article analyzes the effects of parental relationships in divorced families on children's psychology based on a review of scientific literature. The study explores how divorce-related family dynamics impact the emotional and psychological well-being of school-age children. The literature analysis is conducted from philosophical, psychological, and ethnopsychological perspectives, with special attention to the cultural context of Uzbek family values and traditions.